OECD information technology outlook 2006 (OECD Pub. ParisFR, 2006)
Provides member countries with a broad overview of trends and near-term prospects in the information technology (IT) industry; analysis of the growing impact of IT on the economy and society; emerging applications in selected areas of information; and, a review of IT policies and new policy directions.
Keywords: INFORMATION TECHNOLOGY